Influence of HRM Factors on Retention in South India. - Kuttappa, Shoury (Journal of Contemporary Research in Management (JCRM), 2013)
The importance of HR Policies & Practices in the changing business landscape of the 21st century has been spoken about in numerous forums across the globe. There is, clearly, a growing awareness that these aspects of management cannot be pushed under the carpets any longer. Nor can there be a â€œone plan fits allâ€ approach to HR practices any more. Several prominent experts have begun to study this sphere and have brought out many interesting findings to the surface. Â Â Â Â Â Â Â Â Â Â Â Â How does this part of the world (South India) compare with these inputs. The article talks about a few identified HRM Practices and Policies and sees how these influence the decision makers in this region. It is an attempt to bring to the forefront how HR practioners see these factors, as compared to the rest of the world.